Benefits of service learning based on the three pillars of sustainability (Social) - Hassan, Zainudin (Institute of Advanced Scientific Research, Inc., 2020)
Service-learning is an instructional strategy that combines a number of methods to enrich learning and at the same time to get the students to become socially responsible citizens, while improving the communities involved. More often than not, service learning is associated with sustainability, where the activities carried out in its related projects should take into consideration the vibrance of all the three dimensions of sustainability (social, economic and environment) involved in the development. It is important, not only for students, but also everyone in the community to play a part in sustaining the development. However, studies have shown that people tend to drift away in development, hence forgetting to take adequate measures to achieve sustainability. This research explored the experiences of eight postgraduate students on their engagement in service learning projects and the ways they have benefitted from the projects, based on the three pillars of sustainability (social). The data was collected using semi-structured interviews conducted with the students and a thematic approach was used to analyze it. The findings of this research revealed that, the students have personally benefitted from the service learning projects they were involved in. Most of them have improved in their personal growth, social interactions, knowledge about the environment and ways to sustain it. The students even got to learn the simplest ways to raise funds for the community involved without jeopardizing the well-being of the environment. Besides, this research also discovered that, through service learning, the students were able to do charitable work which contributed to the economic dimension. This research concluded that, with a proper planning on service learning projects and commitment from all the stakeholders, service learning can actually help in producing more civilized citizens who have the sense of stewardship. This case study research provides stakeholders an overall understanding on the ways service-learning benefits the students involved based on the social, economic and environment dimensions. This understanding is expected to facilitate advocacy for more service-learning programmes to be conducted on a wider scale to give more youths the opportunities to become active and responsible members of the society who care about sustainability to ensure a better future for everyone.